Modeling and Simulation of the Operation of a Mechanical System which is Affected by Uncertainties. (2016) - Dulau, Mircea; Oltean, Stelian-Emilian; Duka, Adrian-Vasile
Abstract: In control engineering, the mathematical model of the studied process plays an important part. In representing the mathematical model, the inherent errors due to parameter variations define the parametric (structured) uncertainties; therefore there are differences between the mathematical model used in the design process and the real plant. In most cases, the control system needs to stabilize the process and also needs to assure certain performances even in the presence of uncertainties, unmodeled dynamics, disturbance signals and measurement noise, which all make the process vulnerable. This paper shows a method for behavioral modeling and simulation of a gear system, in which the moment of inertia and the friction coefficient represent the parameters which are affected by uncertainties, and are expressed by percentages to the nominal values. For the modeled process, by considering a classical controller, which is tuned experimentally, Matlab is used to represent the sensitivity functions in both time and frequency domains for the nominal cases, for randomly generated samples and for the worst case scenarios.